Magnetic Platelets as a Platform for Drug Delivery and Cell Trapping - Oksana A. Mayorova; Olga I. Gusliakova; Ekaterina S. Prikhozhdenko; Roman A. Verkhovskii; Daniil N. Bratashov (MDPI AG, 2023)
The possibility of using magnetically labeled blood cells as carriers is a novel approach in targeted drug-delivery systems, potentially allowing for improved bloodstream delivery strategies. Blood cells already meet the requirements of biocompatibility, safety from clotting and blockage of small vessels. It would solve the important problem of the patient's immune response to embedded foreign carriers. The high efficiency of platelet loading makes them promising research objects for the development of personalized drug-delivery systems. We are developing a new approach to use platelets decorated with magnetic nanoparticles as a targeted drug-delivery system, with a focus on bloodstream delivery. Platelets are non-nuclear blood cells and are of great importance in the pathogenesis of blood-clotting disorders. In addition, platelets are able to attach to circulating tumor cells. In this article, we studied the effect of platelets labeled with BSA-modified magnetic nanoparticles on healthy and cancer cells. This opens up broad prospects for future research based on the delivery of specific active substances by this method.